The Catholic Family towards Cultural Diversity - Pawlik, Jacek Jan (Studia Warmińskie, 2018)
The article presents the issue of intercultural relations on, selected by the author, examples of meetings in everyday situations between the natives living in a basically Catholic society, in which the model of family life is based on Gospel principles and visitors for whom Christian cultural patterns are usually foreign. The author of the study concludes that every relationship between these two entities is not only an exceptional experience, but also an opportunity for cultural enrichment of the Catholic and the verification of his cultural convictions. The author notes that attitudes that promote fruitful contact (e.g. openness, humbleness, spirit of dialogue), as well as factors that make it difficult (e.g. intolerance, suspicion towards strangers) have their roots in the family home. Therefore, every effort should be made to ensure that young people are taught at home attitudes desirable from the point of view of well-formed relations between representatives of different cultures. At the same time, the author indicates that the course of action that should be taken to shape Catholics’ own references to representatives of non-Catholic cultures, is marked by many official documents of the Roman Catholic Church. One of the most important among them is the document of the Pontifical Council for Interreligious Dialogue and the Congregation for the Evangelization of Peoples “Dialogue and Proclamation” (1991). Summing up the analyzes carried out, the author emphasizes that harmonious life in a multicultural community is not a matter of competence, but is conditioned by building up - particularly in the family home - the right attitudes that guarantee openness and empathy towards another, especially a culturally alien person.